1999
DOI: 10.1073/pnas.96.9.5286
|View full text |Cite
|
Sign up to set email alerts
|

Substance P is expressed in hippocampal principal neurons during status epilepticus and plays a critical role in the maintenance of status epilepticus

Abstract: Substance P (SP), a member of the tachykinin family, is widely distributed in the central nervous system and is involved in a variety of physiological processes including cardiovascular function, inflammatory responses, and nociception. We show here that intrahippocampal administration of SP triggers self-sustaining status epilepticus (SSSE) in response to stimulation of the perforant path for periods too brief to have any effect in control rats, and this SSSE generates a pattern of acute hippocampal damage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 51 publications
3
88
0
Order By: Relevance
“…The contribution of tachykinins in excitotoxic neurotransmission has been proposed for various pathological conditions in the nervous system, including nociception in spinal cord (Saria 1999), epilepsy in hippocampus (Liu et al 1999) and cerebral ischemia in cortex (Stumm et al 2001). Most recent studies demonstrated the co-localization of neuronal nitric oxide synthase (nNOS) and NK-1 receptor in striatal interneurons (Li et al 2001), as well as the direct projections from SP-containing neurons to nNOS-containing interneurons in the striatum (Li et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of tachykinins in excitotoxic neurotransmission has been proposed for various pathological conditions in the nervous system, including nociception in spinal cord (Saria 1999), epilepsy in hippocampus (Liu et al 1999) and cerebral ischemia in cortex (Stumm et al 2001). Most recent studies demonstrated the co-localization of neuronal nitric oxide synthase (nNOS) and NK-1 receptor in striatal interneurons (Li et al 2001), as well as the direct projections from SP-containing neurons to nNOS-containing interneurons in the striatum (Li et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that SP induces glutamate release in the hippocampus 38 and enhances glutamate responses. 39 Thus, the question arises as to whether the SP-induced neuronal cell death we observed was due to glutamate toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that, for certain pathological states such as status epilepticus and neuronal ischemia, a burst of SP release has been reported to occur, prior to neuronal cell death. 29,38,40 For instance, SP is overexpressed in hippocampal neurons during status epilepticus, and intrahippocampal administration of SP triggers pcDNA3.1 NK1R NK1R+SP…”
Section: Discussionmentioning
confidence: 99%
“…Binding 2 , 0.1 mM PMSF, 5 g/ml soybean trypsin inhibitor, and 400 mg/ml bovine serum albumin. The membrane preparation was then irradiated on ice for 40 min using an ultraviolet light at 365 nm (HPR 125-watt lamp) at a distance of 6 to 10 cm.…”
Section: Materials-[[11-mentioning
confidence: 99%
“…is implicated in many physiological and pathophysiological processes including transmission of pain and inflammation but also depression, epilepsy, and angiogenesis (1)(2)(3). These biological effects are mediated via a G-protein-coupled receptor, the NK-1 receptor, which has been cloned in several species (see Ref.…”
mentioning
confidence: 99%